The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1159/000369014
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Hyperinsulinaemic Hypoglycaemia Secondary to a Congenital Portosystemic Shunt

Abstract: Background: Portosystemic shunts (PSS) are abnormal vascular connections between the portal vein or its tributaries and the systemic vein that allow mesenteric blood to reach the systemic circulation without first passing through the liver. PSS can be associated with various syndromes and can lead to serious complications. We report a rare case of a child with PSS and recurrent hypoglycaemia. Case: A 20-month-old girl with Down's syndrome presented with recurrent hypoglycaemic episodes. She had multiple anomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 17 publications
(21 reference statements)
1
14
0
Order By: Relevance
“…The authors described these effects as a result of reduced insulin degradation in the liver [ 6 ]. This effect has also been described in a few other case reports [ 9 , 10 ]. Bas et al postulated an insufficient postprandial hepatic glucose uptake, resulting in early systemic hyperglycemia, leading to an exaggerated insulin secretion [ 9 ].…”
Section: Discussionsupporting
confidence: 79%
“…The authors described these effects as a result of reduced insulin degradation in the liver [ 6 ]. This effect has also been described in a few other case reports [ 9 , 10 ]. Bas et al postulated an insufficient postprandial hepatic glucose uptake, resulting in early systemic hyperglycemia, leading to an exaggerated insulin secretion [ 9 ].…”
Section: Discussionsupporting
confidence: 79%
“…The clinical presentations of CEPS may vary and depend on associated conditions: (1) liver dysfunction and hepatic neoplasms, which may be benign (focal nodular hyperplasia and nodular regenerative hyperplasia) or malignant (liver cancer), may be due to the lack of perfusion and nutrient delivery to the liver [911]. (2) Congenital hepatic shunts can also present together with hepatic encephalopathy, hepatopulmonary syndrome [12], and hypoglycaemia [13]. (3) Increased pressure of the splenic vein and superior mesenteric vein system with complete or partial occlusion of the portal vein can lead to hypersplenism and haemorrhage of the digestive tract.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Hence, it is possible that patients with CPSS have high insulin concentration, especially after meals, because insulin secreted from beta cells flows directly into the systemic circulation. Senniappan et al 4 reported on a 20-month-old girl with CPSS who had hyperinsulinemic hypoglycemia. The hypoglycemia was completely cured after surgical closure of the shunt, and OGTT after surgery showed no hyperinsulinemia.…”
Section: Discussionmentioning
confidence: 99%
“…Some CPSS patients also have hypoglycemia. Recently, Senniappan et al 4 reported on the case of a 20-month-old girl with Down syndrome and CPSS who presented with hyperinsulinemic hypoglycemia, possibly due to lack of insulin degradation in the liver. Herein we describe the case of a 5-month-old boy with post-prandial CHH and type 1 extrahepatic CPSS.…”
mentioning
confidence: 99%